Vertically interconnected network of graphene fluoride for highly thermoconductive and electrically insulating epoxy composites. Issue 11 (18th August 2022) - Thieu, Nhat Anh Thi; Mani, Dineshkumar; Won, Jong Chan; Yon, Kyung‐Yol; Vu, Minh Canh; Kim, Sung‐Ryong
Abstract: Graphene fluoride (GF), a new graphene derivative, is an excellent candidate for thermal management applications, given its exceptional thermal conductivity and superb insulation properties. However, the fabrication of the vertically aligned graphene fluoride (VA‐GF) sheet network is challenging due to its hydrophobic property and complicated surface modification process. In this work, the freeze‐casting method was used to create VA‐GF scaffolds incorporating polyethyleneimine (PEI) as the dispersing agent and binder. Benefiting from the vertical alignment of the GF scaffold, the epoxy composites exhibited the through‐plane thermal conductivity (TC) of 0.96 W m −1 K −1 at 15 vol% of GF loading, corresponding to 465% and 146% enhancement over pure epoxy and randomly distributed GF/epoxy composites, respectively. As a function of frequency, the electrical conductivity of VA‐GF/epoxy composites was also explored at different filler contents. With increasing GF content and frequency, the electrical conductivity of the composites rose from 10 −9 to 10 −8 S m −1 between 10 3 and 10 6 Hz, demonstrating an insulating property of materials. The vertical alignment of GF in a polymer matrix provides an opportunity for the creation of composites with exceptional thermal conductivity in a through‐plane direction and electrical insulation properties, which promotes the development of thermal management materials for electronic devices. Abstract : A vertically aligned and interconnected graphene fluoride (GF) network is immersed in an epoxy matrix forming a through‐plane thermal conductivity of 0.96 W m −1 K −1 at 15 vol% of GF, which is 465% higher than that of pure epoxy, while 20 vol% of randomly distributed GF shows an enhancement of 200% compared to neat epoxy.